2009
DOI: 10.1371/journal.pone.0005959
|View full text |Cite
|
Sign up to set email alerts
|

Immune Regulatory Neural Stem/Precursor Cells Protect from Central Nervous System Autoimmunity by Restraining Dendritic Cell Function

Abstract: BackgroundThe systemic injection of neural stem/precursor cells (NPCs) provides remarkable amelioration of the clinico-pathological features of experimental autoimmune encephalomyelitis (EAE). This is dependent on the capacity of transplanted NPCs to engage concurrent mechanisms of action within specific microenvironments in vivo. Among a wide range of therapeutic actions alternative to cell replacement, neuroprotective and immune modulatory capacities of transplanted NPCs have been described. However, lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
133
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 54 publications
9
133
0
1
Order By: Relevance
“…Furthermore, exclusive targeting of the peripheral immune system has been reported in relapsing EAE in mice after subcutaneous NPC injection (Pluchino et al, 2009b). NPC-injected EAE mice showed significant clinical improvement, despite the absence of injected cells in the CNS.…”
Section: Signaling At a Distance (Endocrine)mentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, exclusive targeting of the peripheral immune system has been reported in relapsing EAE in mice after subcutaneous NPC injection (Pluchino et al, 2009b). NPC-injected EAE mice showed significant clinical improvement, despite the absence of injected cells in the CNS.…”
Section: Signaling At a Distance (Endocrine)mentioning
confidence: 99%
“…Here, stem cells extensively interact with the host immune system to inhibit the activation and proliferation of T cells (Gerdoni et al, 2007), the maturation of DCs (Pluchino et al, 2009b), or the emigration of spleen neutrophils toward the damaged brain (Lee et al, 2008). Overall, these pioneering studies demonstrated the therapeutic efficacy of MSCs and NPCs in animal models of inflammatory damage, but left (partly) open the question of whether or not stem cell integration in the nervous system is indispensable for the therapeutic outcomes observed.…”
Section: Modulation Of Immune Responsesmentioning
confidence: 99%
See 3 more Smart Citations